Nanocube-structured alkaline-earth-metal hexaborides from solid-phase combustion: Application in hydrogen evolution - Jeong, Junmo; Nersisyan, Hayk; Lee, Hyunjoo; Joo, Sin Hyong; Nguyen, Xuan Viet; Suh, Hoyoung; Lee, Jong Hyeon (Elsevier BV, 2026)
Nanocrystals with well-defined exposed facets exhibit distinctive physicochemical properties that are highly beneficial for catalysis, sensing, and energy storage applications. In this study, a rapid solid-phase combustion method was developed for the scalable synthesis of facet-exposed alkaline-earth-metal hexaboride nanocubes (MB₆: M = Ca, Sr, Ba). The exothermic MO–B₂O₃–Mg reaction generates transient high temperatures and a localized molten phase, together with anisotropic growth dynamics, that drive the self-formation of uniform MB₆ nanocubes. Systematic investigations revealed that the cube edge length can be precisely tuned from 0.1 to 1.0 μm by adjusting the CaO content from 0.35 to 1.5 mol, consistent with diffusion-controlled coarsening. The dominance of low-index {100} facets markedly enhances the hydrogen evolution reaction (HER) performance, delivering an overpotential of 220 mV at 10 mA cm−2 and a Tafel slope of 60 mV dec−1 in 0.5 M H₂SO₄. This impressive activity, combined with excellent cycling stability, positions the catalyst among the most competitive non–noble–metal–based HER catalysts. Density functional theory (DFT) analysis is applied to calculate hydrogen adsorption free energies (ΔG*) on Ca-terminated and B-terminated sites and to show charge-transfer properties on the CaB₆ (100) surface. Additionally, the versatility of this method was demonstrated by the successful synthesis of CaB₆-based materials integrated with rare-earth elements and high-entropy hexaborides.